MECHANISMS OF MELATONIN EFFECTS UPON IMMUNE STATE IN EXPERIMENTAL DESYNCHRONOSES PRODUCED UNDER THE LED ILLUMINATION CONDITIONS - M. V. Osikov; O. A. Gizinger; O. I. Ogneva (Медицинская иммунология, 2016)
Disorders of immune state in desynchronosis may be associated with reduced concentrations of melatonin in blood, thus being a prerequisite for pharmacological correction of appropriate homeostatic changes. The purpose of this work was to explore some mechanisms of exogenous melatonin actions upon parameters of innate and adaptive immunity in experimental model of desynchronosis under the conditions of LED illumination. The study was performed with 196 adult guinea pigs. Light desynchronosis was produced by day-and-night illumination of the animals having been continued for 30 days. Melatonin was administered applied per os daily at the total dose of 30 mg/kg. A solution of melatonin in isotonic NaCl solution was prepared from the Melaxen drug (INN: melatonin, “Unipharm Inc.,” USA) ex tempore. To study innate immunity of blood cells, we determined leukocyte numbers, WBC differential counts, and functional activity of phagocytes, as spontaneous and induced NBT test, as well as engulfment of polystyrene latex particles. Th1-specific immune response was studied according to degree of delayed type hypersensitivity reaction; Th2-dependent response was assessed as the numbers of antibody-forming cells in the spleen of the animals after immunization with allogeneic erythrocytes. Serum concentrations of interleukin 4 (IL-4), interferon-gamma (IFNγ), melatonin, and cortisol were measured by enzyme immunoassay, using the “Immulayt 2000” (USA) with guinea pigspecific test systems. It was found that experimental desynchronosis was associated with leukocytosis, lymphoand monocytopenia, activation of oxygen-dependent metabolism of blood phagocytes, suppression of Th1-and Th2-dependent immune response. Desynchronosis was also accompanied by decreased concentrations of serum melatonin, IFNγ and IL-4, along with increased cortisol concentrations. Reduced IFNγ and IL-4 amounts was associated with decreased melatonin concentrations. Suppression of Th1- and Th2-dependent immune response is found to develop in accordance with reduction in IFNγ and IL-4. Melatonin administration in desynchronosis (a total of 30 mg/kg) resulted in recovery of blood leukocyte counts, ROS generation by phagocytes, higher intensity of Th1- and Th2-dependent immune response, cortisol, IFNγ and IL-4 concentrations in blood serum, like as stimulation of blood phagocytic capacity. Restoration of Th1- and Th2-dependent immune response is associated with normalized concentrations of, respectively, IFNγ and IL-4 levels in blood serum.